Neurons Induced From Fibroblasts of c9ALS/FTD Patients Reproduce the Pathology Seen in the Central Nervous System - Bauer, Peter O.; Dunmore, Judith H.; Sasaguri, Hiroki; Matoska, Vaclav (Frontiers in Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are incurable neurodegenerative conditions. A non-coding hexanucleotide (GGGGCC) repeat expansion in the c9orf72 gene is the most common genetic cause of ALS/FTD. We present a cellular model of c9ALS/FTD where induced neurons (iNeurons) are generated within 2 weeks by direct conversion of patients‘ dermal fibroblasts through down-regulation of polypyrimidine-tract-binding protein 1 (PTB1). While sense (S) and anti-sense (AS) intranuclear RNA foci were observed in both fibroblasts and iNeurons, the accumulation of (S) and (AS) repeat-associated non-ATG translation (RANT) products were detected only in iNeurons. Importantly, anti-sense oligonucleotides (ASOs) against the (S) repeat transcript lead to decreased (S) RNA foci staining and a reduction of the corresponding RANT products without affecting its (AS) counterparts. ASOs treatment also rescued the cell viability upon stressful stimulus. The results indicate that iNeurons is an advantageous model that not only recapitulates c9ALS/FTD hallmark features but can also help uncover promising therapeutics.